PROBLEMS AND WAYS TO IMPROVE THE ORGANIZATION OF CARDIOLOGICAL CARE TO THE RURAL POPULATION, IN THE CARDIOLOGISTS OPINION - Ivanyuk, Anatoliy; Kanyura, Alexander (The Ukrainian Scientific Medical Youth Journal, 2020)
to study the state, problems and ways of improving the organization of cardialogical care for the rural population in Ukraine based on the materials of a sociological survey of cardiologists.